Global Health Diplomacy: Between Global Society and Neo-colonialism: The Role and Meaning of "Ethical Lens" in Performing the Six Leadership Priorities - Michele Rubbini (Springer, 2018)
Establishing indicators oriented towards the creation of a global society to the detriment of new forms of neo-colonialism. In the relations between Developed and Emerging Countries as part of the Global Health Diplomacy, there is a risk that the former can adopt behaviors induced by the financial needs of overcoming their crisis. The most relevant Documents by International Organizations and Articles published in the past regarding actions in this area and the forecast of economic growth in various areas of the World are considered and the hypothesis of dual scenarios that may arise from these are postulated. There are two hypothetical scenarios arising from the "six leadership priorities": the search for a Global Society or initiating forms of neocolonialism on the part of developed countries towards emerging ones. If the "economic lens" is to prevail then the developed Countries, would seek to charge their crisis to emerging Ones where a forthcoming significant growth has expected; if the "ethical lens" is to prevail, it will be most likely be the hypothesis of a Global Society where there is a respect of Human Rights in order to drive growth and harmonization of relations between Governments.